On the construction of Chinese stock market investor sentiment index - Gang He; Shuzhen Zhu; Haifeng Gu (Cogent Economics & Finance, 2017)
Measuring investor sentiment has become one of the most widely examined areas in behavioral finance. For the purpose of measuring investor sentiment more accurately, we classify the investor sentiment proxy into six market dimensions for the first time, and construct the investor sentiment monitoring index system. By using PCA method and excluding macroeconomic factors, we construct comprehensive investor sentiment index in Chinese stock market. Our results show this index as a good prediction ability to stock market.
Keywords: 330; investor sentiment; monitoring system; composite index